Factoring sözleşmesi - Kazmacı, Özge Uzun (My University, 2011)
FACTORİNG SÖZLEŞMESİ Factoring işlemi; factoring şirketi, müşteri ve müşterinin borçlusu arasında gerçekleşen üç köşeli bir ilişkidir. Yurt dışı factoring’de, genellikle, bu ilişkiye yurt dışında faaliyet gösteren bir muhabir factor katılır ve ilişki dört köşeli hale gelir. Ancak hem yurt içi, hem yurt dışı factoring açısından, işlemin temelini oluşturan sözleşme, factor ile müşteri arasında yapılan factoring sözleşmesidir. Tezimizin konusunu bu sözleşme oluşturmaktadır. Tezin birinci bölümünde, sözleşmeye konu olan factoring işlemi, bu işlemin türleri işlevleri ve benzer işlemlerden farkları ele alınmıştır. İkinci bölümde, genel olarak factoring sözleşmesi; sözleşmenin tanımı, tarafları, hukuki niteliği, şekli ve tarafların yükümlülükleri incelenmiştir. Üçüncü bölümde, factoring sözleşmesinde müşterinin alacaklarının ve bu alacaklara ilişkin kambiyo senetlerinin factor’e devri ve bunun sonuçları incelenmiştir. Son bölümde de sözleşmenin sona erme nedenleri ve sonuçları üzerinde durulmuştur. Factoring sözleşmesi, kanunda düzenlenmediğinden isimsiz bir sözleşmedir. Her iki tarafa karşılıklı borçlar yüklediğinden, tam iki taraflı bir sözleşmedir. Müşteri alacaklarını genellikle bu sözleşme ile factor’e toptan bir şekilde devrettiğinden, factoring sözleşmesinde borçlandırıcı işlem ve tasarruf işlemi çoğunlukla bir arada bulunur. Uygulamada factoring sözleşmeleri, factor tarafından hazırlanan genel işlem koşullarını içeren standart sözleşmeler şeklinde hazırlanır. Bu sözleşme ile müşteri, işletmesi ile ilgili alacaklarını factor’e devreder ve factor’ün kendisine sunacağı factoring hizmeti karşılığında, faiz, komisyon ve masraf adı altında çeşitli ödemelerde bulunmayı borçlanır. Factor de bu sözleşme ile devraldığı alacakların tahsilini, alacakların muhasebesini tutmayı, vadeden önce ön ödeme yaparak kredi sağlamayı, bazı alacaklar için borçlunun ödeme gücünü garanti etmeyi ve ayrıca kararlaştırılmışsa piyasa araştırması, danışmanlık gibi ek hizmetlerde bulunmayı üstlenir.

FACTORİNG CONTRACT Factoring transaction is a triangular transaction accrued between the factoring company, the customer and the debtor of the customer. At the factoring in abroad, generally, a corrospondent factor having operations in abroad participates into this relationship and this relationship becomes four-cornored. However even for the domestic factoring and even for the factoring in abroad, the contract constituting the base of the transaction is the factoring contract between the factor and the customer. This contract constitutes the subject of our thesis. In the first division of the thesis, the factoring transaction being the subject of the contract, the species and functions of this transaction and the differences from the similar transactions are handled. In the second division, factoring contract in general, the definition of the contract, parties, legal nature, its form and the obligations of the parties are examined. In the third division, the transfer of the receivables of the customer and the bill of exchange related to this receivables to the factor in the factoring contract and the conclusion of this situation is examined. In the last division, the causes of the termination of the contract and the results of the termination are dwelled upon. Factoring contract is an unnamed contract due to the fact that it is not regulated in the legislative act. It is a synallagmatic contract due to its nature that it imposes obligations for both parties. The promissory transaction and the dispositive transaction are mostly together due to the fact that generally customer transfers customers’ credits to the factor in this contract wholly. In practise, factoring contracts are prepared by the factor to be standart contracts including the general transaction terms By this contract, customer transfers customer’s enterprises’receivables to the factor and becomes indebted to make payments under the name of the interest, commision and the cost in return for the factoring service to be provided by the factor for the customer. Factor commits to collect the receivables which are transferred by the factor by this contract, conduct the accounting service for the receivables, provide credit by making payments before the due date, guarantee the payment ability of the debtor for some kind of receivables and if it is mutually agreed factor agrees to serve additional services such as market research and consultancy services.
Keywords: Factoring Sözleşmeleri; Özel Hukuk; Sözleşmeler_Hukuk